The hare and the tortoise - Kelly;Miles (Thaxted Miles Kelly Publishing Ltd, 2016)
The much-loved tale of The Hare and the Tortoise has been beautifully captured by Monika Filipina's fun, quirky illustrations. Every page showcases delightful full-bled artwork, packed with charm and detail that will enthrall children aged 3+. The story has been simply retold to appeal to young readers and listeners alike